Evaluation of the smart mobility dimension, from challenges and best practices to recommendations - Junqueira, Rodolfo Ribeiro (2021)
To face challenges like rising urban population and CO2emissions, EU cities are implementing innovative and greener mobility solutions. Lisbon’s worst Smart City dimension, Smart Mobility has the potential to improve the city’s life. Smart Mobility, a technology-based market, is growing at a CAGR of 20% until2026. This project resorts to best practices analyses and conducting interviews and surveys, to produce recommendations on Individual Mobility, targeting Road Management and Parking; on Shared Mobility, regarding Public Transports and Shared-Mobility Apps; and on Mobility Administration, endorsing a Gamified app system and usage of Green Bonds.